Program Di Ma’had Izzatuna Putri Palembang - Indah Nurseha; Rendi Sabana (Cordova Journal : languages and culture studies, 2022)
This study aims to describe and analyze data about the ishlahul lughoh program, planning, implementation process, and evaluation in the implementation of the ishlahul lughoh program at Ma'had Izzatuna Putri Palembang. This research was motivated by the many errors in speaking Arabic for students at Ma'had Izzatuna Putri Palembang, a program had been implemented to correct errors in the language of female students, namely an ishlahul lughoh program. This study used a qualitative approach with a descriptive method. The data collection techniques in this research use observation, interview, and documentation methods. Data analysis used reduction, presentation, and conclusion. Test the validity of the data using triangulation. The results in this study First; Planning for the ishlahul lughoh program, namely the teacher and the language section prepare several plans starting from preparing the material to be given, and the methods used. Second; The process of implementing the ishlahul lughoh program started with the teacher mentioning the wrong sentence or language first then giving the correct language and examples in the form of a sentence. Third; Evaluation of the ishlahul lughoh program with evaluations held every day by the language section by supervising female students in speaking during daily activities and evaluations held at the end of each semester. The form of the end of semester exam questions was in the form of a written exam. The conclusion from this study is that the planning, process and evaluation of the islahul lugho program was very good and continues to grow in this institution so that it has an impact on the process of developing and improving the language of female students in the process of learning Arabic.